PERANCANGAN SISTEM INFORMASI PENJAMINAN MUTU PERGURUAN TINGGI BIDANG SUMBER DAYA MANUSIA - Ade Tutty R Rosa (Media Nusantara, 2019)
Human resources (HR) in the university environment consisting of lecturers andsupporting staff have a very strategic position, because it has a direct influenceon the learning process, graduate quality and competitive output patterns.The effectiveness of performance in the teaching and learning process and theimprovement of the academic atmosphere are strongly influenced by the qualitystandardization to be achieved as well as the quality assurance process that must be carried out by a university, one of them in the field of human resources(HR). The requirements that must be fulfilled so that the implementation of theHR quality assurance system in a university can be implemented properly is theavailability of an accurate database that can be used in every decision making.For this reason, it is necessary to develop an HR quality assurance informationsystem in a university environment. This HR quality assurance informationsystem can function to make it easier for universities to carry out qualityassurance, so that the quality assurance process can be carried out through stages that are strung together and supported by databases (database), management information systems, and integrated decision support systems . The stages carried out in designing this information system include needs analysis, process model design, software requirements analysis, and design.